ANALISIS YURIDIS FRAUD SEBAGAI ALASAN PEMBATALAN KONTRAK DALAM HUKUM PERDATA INDONESIA - Agusto Benaya Sembiring; Fernando Travis; Oscarolus Sembiring; Jamalum Sinambela (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This article discusses fraud as a legal ground for contract annulment from the perspective of Indonesian civil law. Using a normative juridical approach, the article examines the provisions of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata), particularly Articles 1321 and 1320, and analyzes several court decisions as jurisprudence. The findings indicate that fraud constitutes a defect of will (wilsgebrek) that can invalidate a contract if it is proven to have influenced the consent of one of the parties. The article recommends strengthening evidentiary instruments related to fraud in contractual relationships to safeguard legal certainty and justice for the injured party.